Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find which expression is equivalent to [tex]\(\left(\frac{u}{v}\right)(x)\)[/tex] given that [tex]\(u(x) = x^5 - x^4 + x^2\)[/tex] and [tex]\(v(x) = -x^2\)[/tex], let's perform the following steps:
1. Identify the expressions for [tex]\(u(x)\)[/tex] and [tex]\(v(x)\)[/tex]:
- [tex]\(u(x) = x^5 - x^4 + x^2\)[/tex]
- [tex]\(v(x) = -x^2\)[/tex]
2. Form the quotient [tex]\(\left(\frac{u}{v}\right)(x)\)[/tex]:
[tex]\[ \left(\frac{u}{v}\right)(x) = \frac{x^5 - x^4 + x^2}{-x^2} \][/tex]
3. Divide each term in the numerator by the term in the denominator [tex]\(-x^2\)[/tex]:
[tex]\[ \left(\frac{u}{v}\right)(x) = \left(\frac{x^5}{-x^2}\right) + \left(\frac{-x^4}{-x^2}\right) + \left(\frac{x^2}{-x^2}\right) \][/tex]
4. Simplify each term individually:
[tex]\[ \frac{x^5}{-x^2} = -x^{5-2} = -x^3 \][/tex]
[tex]\[ \frac{-x^4}{-x^2} = x^{4-2} = x^2 \][/tex]
[tex]\[ \frac{x^2}{-x^2} = -1 \][/tex]
5. Combine these simplified terms:
[tex]\[ -x^3 + x^2 - 1 \][/tex]
So, the expression equivalent to [tex]\(\left(\frac{u}{v}\right)(x)\)[/tex] is [tex]\( -x^3 + x^2 - 1 \)[/tex].
Therefore, the correct option is:
[tex]\[ -x^3 + x^2 - 1 \][/tex]
1. Identify the expressions for [tex]\(u(x)\)[/tex] and [tex]\(v(x)\)[/tex]:
- [tex]\(u(x) = x^5 - x^4 + x^2\)[/tex]
- [tex]\(v(x) = -x^2\)[/tex]
2. Form the quotient [tex]\(\left(\frac{u}{v}\right)(x)\)[/tex]:
[tex]\[ \left(\frac{u}{v}\right)(x) = \frac{x^5 - x^4 + x^2}{-x^2} \][/tex]
3. Divide each term in the numerator by the term in the denominator [tex]\(-x^2\)[/tex]:
[tex]\[ \left(\frac{u}{v}\right)(x) = \left(\frac{x^5}{-x^2}\right) + \left(\frac{-x^4}{-x^2}\right) + \left(\frac{x^2}{-x^2}\right) \][/tex]
4. Simplify each term individually:
[tex]\[ \frac{x^5}{-x^2} = -x^{5-2} = -x^3 \][/tex]
[tex]\[ \frac{-x^4}{-x^2} = x^{4-2} = x^2 \][/tex]
[tex]\[ \frac{x^2}{-x^2} = -1 \][/tex]
5. Combine these simplified terms:
[tex]\[ -x^3 + x^2 - 1 \][/tex]
So, the expression equivalent to [tex]\(\left(\frac{u}{v}\right)(x)\)[/tex] is [tex]\( -x^3 + x^2 - 1 \)[/tex].
Therefore, the correct option is:
[tex]\[ -x^3 + x^2 - 1 \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.